A Petri net asset management framework for railway switches and crossings. (March 2023) - Litherland, Jack; Andrews, John
Switches and Crossings (S&C) are a fundamental part of any railway network, they allow trains to switch between tracks and to cross over other tracks. They consist of various electrical and mechanical components to which there is a substantial maintenance cost. Failure of an S&C unit can cause significant disruption to traffic and have large financial implications. Therefore, planning their maintenance is of critical importance to railway asset managers. This research proposes an asset management framework, which models the degradation, failure, inspection and maintenance for the S&C unit. The framework comprises nine Petri net sub-models for the S&C component availability and predicts the number of maintenance interventions in a given time period. This can be used to inform maintenance decision making, with the aim of reducing the life cycle cost of the S&C.